Dual Regeneration of Muscle and Nerve by Intramuscular Infusion of Mitochondria in a Nerve Crush Injury Model. (18th November 2021) - Sheu, Meei-Ling; Shen, Chiung-Chyi; Tsou, Hsi-Kai; Yang, Meng Yin; Su, Hong-Lin; Sheehan, Jason; Chang, Ming-Hong; Chen, Hong-Shiu; Pan, Hung-Chuan
Graphical Abstract: